Distance Measurement for the Indoor WSN Nodes Using WTR Method - Zheng Zhang; Junxiao Zhu; Jiabiao Ruan; Gangbing Song (International Journal of Distributed Sensor Networks)
Time reversal (TR), which leads various multipath signals to focus spatiotemporally on arbitrarily complex propagation environments, can resist signal multipath delay and attenuation which is caused by inhomogeneous complex environments. In this paper, the windowed time reversal (WTR) method for distance measurement between the wireless sensor network (WSN) nodes is proposed based on TR. In the WTR, the main lobe of the channel response is captured by a window. WTR not only takes advantage of the spatiotemporal focus features of TR, but also compensates the multipath effect to eliminate various factors from the environment. WTR can recover the favorable symmetry of the main lobe of channel response, thereby accurately measuring the times-of-arrival (TOA) of the electromagnetic wave and distance between WSN nodes. By analyzing the characteristics of the time reversal operator, the theoretical basis of the WTR is given in this paper. An algorithm for node distance measurement with WTR in indoor environments is described and a large number of simulations with various environments are carried out. The errors for the proposed WTR have been analyzed. Simulation results show that ranging errors by WTR are less than 1% no matter how many obstacles are in the indoor environment.